Engineering of proteolytically stable NADPH-cytochrome P450 reductase - Bonina, T. A.; Gilep, A. A.; Estabrook, R. W.; Usanov, S. A. (Biochemistry (Moscow), 2005)
NADPH-cytochrome P450 reductase (CPR) is a membrane-bound flavoprotein that interacts with the membrane via its N-terminal hydrophobic sequence (residues 1-56). CPR is the main electron transfer component of hydroxylation reactions catalyzed by microsomal cytochrome P450s. The membrane-bound hydrophobic domain of NADPH-cytochrome P450 reductase is easily removed during limited proteolysis and is the subject of spontaneous digestion of membrane-binding fragment at the site Lys56-Ile57 by intracellular trypsin-like proteases that makes the flavoprotein very unstable during purification or expression in E. coli. The removal of the N-terminal hydrophobic sequence of NADPH-cytochrome P450 reductase results in loss of the ability of the flavoprotein to interact and transfer electrons to cytochrome P450. In the present work, by replacement of the lysine residue (Lys56) with Gln using site directed mutagenesis, we prepared the full-length flavoprotein mutant Lys56Gln stable to spontaneous proteolysis but possessing spectral and catalytic properties of the wild type flavoprotein. Limited proteolysis with trypsin and protease from Staphylococcus aureus of highly purified and membrane-bound Lys56Gln mutant of the flavoprotein as well as wild type NADPH-cytochrome P450 reductase allowed localization of some amino acids of the linker fragment of NADPH-cytochrome P450 reductase relative to the membrane. During prolong incubation or with increased trypsin ratio, the mutant form showed an alternative limited proteolysis pattern, indicating the partial accessibility of another site. Nevertheless, the membrane-bound mutant form is stable to trypsinolysis. Truncated forms of the flavoprotein (residues 46-676 of the mutant or 57-676 of wild type NADPH-cytochrome P450 reductase) are unable to transfer electrons to cytochrome P450c17 or P4503A4, confirming the importance of the N-terminal sequence for catalysis. Based on the results obtained in the present work, we suggest a scheme of structural topology of the N-terminal hydrophobic sequence of NADPH-cytochrome P450 reductase in the membrane.